Analisis Faktor Pengaruh dalam Keberlanjutan Pengelolaan Sampah di TPST Kota Bandung dengan Metode Structural Equation Modelling (SEM) - Rizal Husni Nurulloh; I Made Wahyu Widyarsana (Jurnal Serambi Engineering, 2024)
Problems with infrastructure services such as waste management arise due to the rapid population growth and various other human activities. Based on SIPSN data, in 2022 managed waste reached 96.78% or 3% of waste ended up in the Sarimukti Landfill. The condition of Sarimukti Landfill which is already over capacity, will be closed in 2024. One of the efforts made by the Bandung City Government is to build Material Recovery Facility (MRF). In addition, the MRF development program was initiated by the Improvement of Solid Waste Management to Support Regional Areas and Metropolitan Cities (ISWMP). The purpose of this study is to determine the influential factors in waste management in the ISWMP program MRF (Cicukang Holis MRF) and non-program (Babakan Sari MRF). The focus of this research is the sustainability of the MRF program with the target respondents being the beneficiaries. Data were collected through observation, questionnaires, and interviews. This research analyzes 5 (five) aspects of waste management in settlements, namely technical operations, regulations, community participation, financing, and institutions. The method used is the SEM (Structural Equation Modeling) method to confirm the most influential factors in waste management in the MRF. The results showed that the most influential factor in waste management in MRF is the financing aspect.